Performance Analysis of the Water Supply System in Salina Cruz, Oaxaca - Ponce Martínez, Adriana Eneida (2023)
The aim of this work is to analyze the performance of a drinking water supply system. The data was collected by the city’s water system staff. The water supply system performance was measured using Six Sigma metrics on an EPANET simulation. Initial conditions were compared to future scenarios under implemented changes. The results showed that the current water supply is incapable of satisfying user requirements. The water shortage is not due to a lack of extraction but to losses of up to 43% that occur within the system itself. However, according to the simulation, the system’s capacity can be improved by applying changes to the pumping and distribution conditions. Inspection and maintenance of the network is a priority in order to mitigate large water losses. Increasing extraction would mask the waste problem and lead to an overexploitation of the well.